Essentials of autism spectrum disorders evaluation and assessment - Saulnier, Celine A.; Ventola, Pamela E. (Hoboken, New Jersey Wiley, 2024)
"In the Essentials of Autism Spectrum Disorder Assessments, the authors illustrate a comprehensive developmental model for multi-disciplinary diagnostic evaluations for ASD. This model is derived from years of experience in conducting multidisciplinary diagnostic evaluations for ASD following standards of best practice. Given the neurodevelopmental nature of ASD, symptoms unfold over the course of early development and subsequently impact multiple areas of functioning. For this reason, the developmental skills that ultimately need to be assessed often require clinicians with different disciplinary expertise. Thus, in this Essentials series, the authors outline the components of best practices while highlighting the necessity of integrating findings from multiple sources so that one comprehensive and cohesive diagnostic formulation can be provided for an individual's optimal care. We also emphasize the need to take a strengths-based approach to capitalize upon the innumerable exceptional abilities and characteristics of ASD that should be honed to foster more vulnerable skills"--
Includes index.
Keywords: Autism spectrum disorders